A Novel Twofold Symmetry Architected Metamaterials with High Compressibility and Negative Poisson's Ratio. Issue 5 (28th February 2021) - Khan, Kamran A.; Alshaer, Mohammad H.; Khan, Muhammad Ali
Abstract : This study presents the compression response of additively manufactured novel soft porous structures with architected microstructure. Six porous additively manufactured architected periodic structures with two‐fold and four‐fold symmetry were considered. The effect of pore shape and fold symmetry of microstructure on the non‐linear response of a square array of architected pores in a soft polymeric matrix is experimentally investigated. The digital image correlation (DIC) is used for investigating the evolution of strains and deformation during uniaxial tensile tests and compression tests of porous structures. Compression induced instability lead to negative Poisson's ratio, and compaction of porous structures, which is found to depend not only on the shape of the architecture but also the fold symmetry exists in the microstructure's unit cell. Unique architectures with multiple buckling modes and shape transformation are also observed. Two‐fold symmetry structures are found to buckle at lower strains compared to the four‐fold symmetric structure at the same porosity level and produced high compaction and negative Poisson's ratio. The results showed that in addition to pore shape, the fold symmetry could be used effectively to design a new class of soft, active, and reconfigurable devices over a wide range of length scales with desired characteristics. Abstract : This study investigates the compressibility and auxeticity of a new family of soft porous architected periodic structures with two‐fold and four‐fold symmetries. The results show that in addition to pore shape, the two‐fold symmetry can be used effectively to design soft reconfigurable devices over a wide range of length scales with higher compressibility and negative Poisson's ratio.